The role of actively open-minded thinking in willingness to take civic and political action on genome-edited food in the United States and Switzerland - Segrè Cohen, Alex; Bearth, Angela; Otten, Caitlin Drummond (Frontiers in Psychology, 2025)
Actively open-minded thinking (AOT) is a set of standards for good thinking, including avoiding overconfidence and a willingness to change one’s mind in response to new information. While AOT is theorized to aid individuals in navigating complex and polarizing issues, little prior literature has examined the role of AOT in public responses to emerging technologies. This study examines how engagement in AOT relates to civic and political action on genome editing. This controversial technology modifies plant genes for improved traits, offering transformative possibilities but bearing associated risks and uncertainties. We conducted surveys in the United States and Switzerland, two countries with different regulations toward genome-edited foods. We find inconsistent evidence for predictions between AOT and willingness to engage in actions supporting or opposing genome editing; further, in several cases, relationships varied by country. We discuss the implications for future research on AOT and public engagement in emerging technologies.